Sinergitas Orang Tua Dan Guru Pendidikan Agama Islam Dalam Penanaman Akhlak SIswa Kelas X di SMK Negeri 1 Kalibawang Wonosobo - Aisyah Purwandari; Mukromin Mukromin; Faisal Kamal (Jurnal Budi Pekerti Agama Islam, 2024)
The synergy between teachers and parents is now absolutely considered in teaching and learning activities and outside of it. In reality, in every teaching process or outside of teaching, teachers need support and cooperation from the family (parents). This research aims to determine the synergy between parents and Islamic Religious Education teachers in cultivating communication and discipline morals in class X students at SMK Negeri 1 Kalibawang Wonosobo. To find out the importance of synergy between parents and Islamic Religious Education teachers in instilling communication and discipline in class X students at SMK Negeri 1 Kalibawang Wonosobo. To understand the supporting and inhibiting factors for the synergy of parents and Islamic Religious Education teachers in instilling communication and discipline in class X students at SMK Negeri 1 Kalibawang Wonosobo. This research uses a qualitative type of research using a descriptive approach. Qualitative research is research that uses observation, interviews, content analysis and data collection methods. The location of this research is SMK Negeri 1 Kalibawang Wonosobo. After the data is collected, it is then analyzed using data analysis, namely, data reduction, data presentation and conclusions. The results of this research show the process of synergy between parents and Islamic Religious Education teachers in instilling communication morals and discipline in class X students at SMK Negeri 1 Kalibawang Wonosobo. First, the synergy between parents and Islamic Religious Education teachers in cultivating students' communication and discipline morals is not optimal. Second, the synergy between parents and Islamic Religious Education teachers is very important so that good communication can be established to direct students, instill communication morals and student discipline so that teachers can know students' activities at home and parents can also know students' activities at school. Third, the supporting factor is the presence of parents and teachers who are ready to educate and direct students. Inhibiting factors are parents' lack of attention to their children's social environment, lack of synchronization of policies at school and at home so that children do not make good use of their time.